KARAKTERISTIK PRODUK CAIR CO-PYROLYSIS SAMPAH PLASTIK DAN PELUMAS BEKAS - Ilyas, Dede Muhamad Ilyas; Mustofa Kamal, Dianta; Amatullah Fatin, Shafa; Susanto, Iwan; Prasetya, Sonki (Politeknik Negeri Jakarta, 2024)
The increasing usage of plastic is proportional to the amount of plastic waste today. The plastic usage makes the human live easier especially for packaging purposes. However, it also has a negative impact to the environment. This is due to it cannot easily decompose. Therefore, it can reduce the level of soil fertility. Besides plastic, lubricant waste from motor vehicles can induce an environmental problem as well since it is categorized of hazardous material (B3) waste. Currently, the use of plastic waste has been widely carried out by correlating into liquid fuel through thermal cracking or pyrolysis treatment. It produces liquid and it can be used as an alternative liquid fuel. This study uses the co-pyrolysis method for treating the used plastic waste with used lubricants. The composition ratios used are 10:0, 10:2, 10:4, 10:6, and 10:8. The highest acquisition of liquid products was in the composition ratio of 10:6 as much as 24.67% with a calorific value of 11015.33 cal/g. Then the highest calorific, density, and viscosity values were obtained, namely at the 10:8 composition ratio of 11061.67 cal/g, 0.8906 g/mL, and 0.927 cSt. It was concluded that the mixing of used lubricants in the co-pyrolysis of LDPE plastic waste was able to increase the calorific value of the liquid product produced.